ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 19/PUU- XII/2014 TERHADAP TAFSIRAN FRASA “KOMITE OLAHRAGA” - Aisyah Hatta Lianda; Dodi Haryono; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
KONI filed a lawsuit through the Constitutional Court to conduct a judicial review ofthe SKN Law with constitutional case register Number 19/PUU-XII/2014, one of the objectsof testing is Article 36 paragraphs (1) and (3) of the SKN Law related to the phrase